2021
DOI: 10.1021/acs.jpcc.1c03410
|View full text |Cite
|
Sign up to set email alerts
|

Computational Prediction of Mechanical Properties of PA6–Graphene/Carbon Nanotube Nanocomposites

Abstract: Polyamide 6 (PA6) is a popular semicrystalline thermoplastic with good strength, stiffness, mechanical damping, wear resistance, and an excellent performance-to-cost ratio. Performance of PA6 materials can be improved with the inclusion of graphene (G) and carbon nanotubes (CNT). In this study, molecular dynamics (MD) simulations with INTERFACE and reactive INTERFACE force fields (IFF and IFF-R) were used to predict the mechanical response of amorphous PA6−CNT/G nanocomposites as a function of CNT/G loading. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…IFF-R replaces the traditional harmonic bond-stretching potential with a morse potential to model covalent bond dissociation in response to large local mechanical deformations. Pisani et al 30 used IFF-R to simulate polyamide nanocomposites, and Odegard et al 31 demonstrated the capability of IFF-R for accurately predicting mechanical properties of fully cured epoxy systems. However, IFF-R has not yet been used to simulate partially cured epoxy systems.…”
Section: Introductionmentioning
confidence: 99%
“…IFF-R replaces the traditional harmonic bond-stretching potential with a morse potential to model covalent bond dissociation in response to large local mechanical deformations. Pisani et al 30 used IFF-R to simulate polyamide nanocomposites, and Odegard et al 31 demonstrated the capability of IFF-R for accurately predicting mechanical properties of fully cured epoxy systems. However, IFF-R has not yet been used to simulate partially cured epoxy systems.…”
Section: Introductionmentioning
confidence: 99%
“…Unless otherwise stated, all visualizations of the atomic structure were performed with the OVITO software . The nonreactive class 2 INTERFACE force field (IFF) was used for densifying, polymerizing, and equilibrating the PA6 systems. , The recently developed reactive IFF or IFF-R was used for the deformation simulations. IFF-R incorporates the Morse potential for fast, accurate bond scission capabilities useful for large deformations.…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…Therefore, very often molecular dynamics (MD) simulations have been employed to capture the interactions between the NPs and the polymeric material (in both uncured and cured states). 75,[79][80][81][82][83][84][85][86][87][88][89][90][91][92] Typically, these interactions consist of non-bonded van der Waals (vdW) and electrostatic interactions: for cases where these interactions cannot be obtained from a priori known force fields, one needs to employ ab initio MD simulations for obtaining these force fields. 75 These intermolecular interactions dictate the NP dispersibility inside the surrounding polymer structure.…”
Section: Forces and Interactions At Play Inside A Magnetic Nanopartic...mentioning
confidence: 99%
“…A detailed understanding of the non-bonded interactions is crucial for modulating such behavior, which in turn dictates the overall properties of the nanocomposites. MD simulation studies have shed light on a variety of issues such as (a) the distribution of polymeric chains around the NPs, 81 (b) the dynamics (e.g., diffusivity) and mean distribution of the NPs inside the polymeric matrix (both in entangled and nonentangled states), 82 (c) the effect of NP functionalization on the polymer structure and dynamics, 83 and (d) the average properties of the nanocomposite, such as the elasticity, 84 thermal conductivity, 85 glass transition temperature, 86 adhesive properties, 87 bulk and Young's moduli, 88 load transfer capabilities, 89 creep properties, 90 self-healing behavior 91 (such average properties are generated by appropriate post-processing of the trajectory data for the polymeric material and the NPs), etc.…”
Section: Forces and Interactions At Play Inside A Magnetic Nanopartic...mentioning
confidence: 99%